Ordered Mesoporous Silica Monoliths as a Versatile Platform for the Study of Magnetic and Photomagnetic Prussian Blue Analogue Nanoparticles. Issue 10 (27th February 2017) - Moulin, Robinson; Delahaye, Emilie; Bordage, Amélie; Fonda, Emiliano; Baltaze, Jean‐Pierre; Beaunier, Patricia; Rivière, Eric; Fornasieri, Giulia; Bleuzen, Anne
Abstract: Invited for the cover of this issue is the group of Anne Bleuzen at Institut de Chimie Moléculaire et des Matériaux d'Orsay, Université Paris‐Saclay, France. The cover image shows the versatility of the chemistry that can be developed in the ordered pores of silica monoliths. Abstract : These molecular materials are particularly interesting for their potential applications in electronic devices… Read more about the story behind the cover in the Cover Profile and about the research itself on page 1303 ff (DOI:10.1002/ejic.201601196 ).